2010
DOI: 10.1021/jp109039v
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Formation in Novel Carotenoid Metal Ion Complexes of Astaxanthin

Abstract: The carotenoid astaxanthin forms novel metal ion complexes with Ca2+, Zn2+ and Fe2+. MS and NMR measurements indicate that the two oxygen atoms on the terminal cyclohexene ring of astaxanthin chelate the metal to form 1:1 complexes with Ca2+ and Zn2+ at low salt concentrations < 0.2 mM. The stability constants of these complexes increased by a factor of 85 upon changing the solvent from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 49 publications
(121 reference statements)
4
93
0
1
Order By: Relevance
“…both pathways will form carotenoid neutral radicals (b-CAR Å and HO-b-CAR-H Å ) (Scheme 3). Recently, Kispert et al [24,[46][47][48][49][50] have extensively investigated the stabilities of different carotenoid neutral radicals formed via proton loss from various positions. For example; based on theoretical calculations and experimental results, the most energetically favorable positions for proton loss from b-CAR-H Å+ , to form b-CAR Å , are 4, 4 0 and methyl groups at 5 and 5 0 positions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…both pathways will form carotenoid neutral radicals (b-CAR Å and HO-b-CAR-H Å ) (Scheme 3). Recently, Kispert et al [24,[46][47][48][49][50] have extensively investigated the stabilities of different carotenoid neutral radicals formed via proton loss from various positions. For example; based on theoretical calculations and experimental results, the most energetically favorable positions for proton loss from b-CAR-H Å+ , to form b-CAR Å , are 4, 4 0 and methyl groups at 5 and 5 0 positions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant mechanism of carotenoids is through quenching of singlet oxygen and subsequently interacting with free radicals. (22) The limitations of this study are firstly, that the sampling was done in stages, since not all of the mice were found to be pregnant. Secondly, that several oxidative stress parameters were not measured, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Polyakov et al (2010) showed that ASTA and its mono-and dication forms can chelate Ca 2+ , Zn 2+ , and Fe 2+ ions, although the lifetime of the radical ions formed electrochemically decreased in comparison to uncomplexed ASTA. Moreover, due to its spatial orientation perpendicular to the plane of lipid bilayers, ASTA increases the hydrophobicity in the central core of biological membranes, with several proposed biochemical/physiological consequences (Gabrielska & Gruszecki, 1996).…”
Section: Biosynthesis and Biological Properties Of Astaxanthinmentioning
confidence: 99%